Conversion in grammar and dictionary: A basic for recognizing conversion in lexicographic practice - Legan Ravnikar, Andreja (Slavia Centralis, 2021)
In this paper, we analyze conversion as one of the ways of creating a new lexeme without changing its morphemic structure, in which the meaning changes in proportion to the changed syntactic role and grammatical properties of the base lexeme. In the 16th century, conversion was an important method for the expansion of the literary language vocabulary, so it was necessary to formulate criteria for recognizing and proving conversion in order to show converted lexemes in independent dictionary entries. The analysis of the converted lexeme includes the identification of new grammatical (morphological) categories, syntactic roles and semantic changes in relation to the base lexeme, and the discovery of new interlexemic relations.